A new plant community with the strictly endemic "Cirsium alpis-lunae" (Asteraceae) in the Northern Apennines (Italy) and considerations on the alliances "Senecionion samniti" and "Adenostylion alpinae" - Viciani, Daniele; Lazzaro, Lorenzo; Gonnelli, Vincenzo; Lastrucci, Lorenzo (Mediterranean Botany, 2019)
We conducted a phytosociological study of the particular coenoses with presence of Cirsium alpis-lunae, a strictly endemic species living in marly-arenaceous montane screes of the Apennines between Tuscany, Emilia-Romagna and Marche. We surveyed all the reported locations and analyzed the coenological and ecological features of the communities by means of standard statistical methods, describing a new association, Laserpitio latifolii-Cirsietum alpis-lunae. We attributed the new association to Mulgedio-Aconitetea, but we noted in the literature some nomenclatural misinterpretations concerning the syntaxonomic treatment of this Apennine vegetation at the order and alliance level. We found that Adenostylion alpinae is the most suitable alliance to encompass Laserpitio latifolii-Cirsietum alpis-lunae and it cannot be considered a synonym of Senecionion samniti. Senecionion samniti was here lectotypified, and seems to be closer to Molinio-Arrhenetheretea than to Mulgedio-Aconitetea.